Optimalisasi Hak Perempuan dalam Perceraian Melalui Mediasi Oleh Mahkamah Syar’iyah Blangpidie - Muna Santri (Publikasi Indonesia, 2023)
The authority of the Shar'iyah Court in the field of marriage, has a lot to do with the interests of women. The verdicts born from these cases are expected to be able to fulfill women's rights after divorce. This study aims to determine the legal regulation on the position of women's rights after divorce and to determine the efforts of the Blangpidie Shar'iyah Court in optimizing the fulfillment of women's rights after divorce. The method used is empirical juridical, which is a legal research method that functions to be able to see the law in a real sense and examine how the law works in a community environment. The type of research is descriptive, the type of data used is primary data and secondary data consisting of primary legal material and secondary legal material. The data collection method uses field study methods by conducting interviews and observations. The data analysis method is using the deductive analysis method. The respondents of this study were Judges at the Blangpidie Shar'iyah Court. The results showed that the position of women's rights after divorce is regulated in Law No. 1 of 1974 as contained in Article 41 letter (c) of the Marriage Law, namely the court can order the ex-husband to provide living expenses or determine an obligation for the ex-wife, as explained in Article 149 of the Compilation of Islamic Law, the ex-husband is obliged to provide iddah bread, mut'ah, and pay off the dowry still owed. The efforts of the Blangpidie Shar'iyah Court in optimizing the fulfillment of women's rights after divorce are that the judge gives a stern warning to the husband at the time of the talaq pledge, if the husband does not provide or does not fulfill the wife's rights that have been agreed in mediation, which has been stipulated in the decision and if there is no affirmation of the talaq pledge, the decision will fall and the husband and wife will not divorce.